Analysis and Simulation of Meshing Force of Main Chain Drive in Baling Process of Round Baler - Lü Beixuan; Chen Yuren (Jixie chuandong, 2018)
The calculation of meshing force between chain links and sprocket is one of the chain transmission dynamics research focus. An approximate equation of sprocket meshing force is derived,under the condition of the local deformation before and after a single roller engaged with the tooth. Taking the main chain drive of a certain round balers as the research object,the dynamic characteristics and meshing force of main chain transmission system with multi-driven wheels in baling process of round balers under the condition of actual load torque are obtained through the simulation,the dynamics characterization of the chain drive system is analyzed and the validity of the model is verified,which present a certain operational method for actual agricultural machinery design.